Efforts to Improve Students' Religious Character in Islamic Education Learning by Implementing Role Playing Models at SD Negeri 1 Lambheu - Mursyidah; Seri Keumalawati (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve students’ religious character in Islamic Education learning through the implementation of the Role Playing model at SD Negeri 1 Lambheu. The research was conducted using a classroom action research (CAR) approach, which was carried out in two cycles, each consisting of planning, action, observation, and reflection stages. The participants were 25 fifth-grade students in the 2024/2025 academic year. Data were collected through observation, interviews, and documentation, and analyzed using both qualitative and quantitative descriptive methods. The results revealed a significant improvement in students’ religious character after the application of the Role Playing model. In the first cycle, the average score of students’ religious character was 71.20, increasing to 86.80 in the second cycle, indicating a 21.9% improvement. Qualitative data also showed enhanced attitudes of honesty, responsibility, cooperation, and respect among students during learning activities. The use of Role Playing allowed students to experience and reflect on moral values through dramatization and real-life scenarios, fostering deeper understanding and internalization of Islamic teachings. This study concludes that the Role Playing model is effective in developing students’ religious character in Islamic Education learning. Therefore, teachers are encouraged to apply this interactive and reflective approach as an alternative method to improve students’ moral and spiritual development in primary education.